The MacPhail Family Aboriginal Pride Program of Calgary - Pinnow, Joanne; Gauthier, Shane R. (First Peoples Child & Family Review, 2011)
Since 1997, certain schools within Calgary have adopted the MacPhail Aboriginal Pride Program. This pilot program intends “to increase graduation rates among Aboriginal students, which historically have been lower than that of their non-Aboriginal peers. Its approach is based on the premise that students who bond and relate to their school environment are more likely to stay in school and succeed academically” (Calgary United Way, 2010). The Aboriginal population has been growing quickly, and Aboriginal children account for a growing proportion of all of the children in Canada (O’Donnel, 2006, p. 65). However, despite growing numbers, many Aboriginal children who live off reserve are being raised in communities where Aboriginal people represent only a small minority. In these communities, it is difficult to maintain ties to Aboriginal traditions and cultures. The MacPhail Aboriginal Pride Program attempts to help Aboriginal children and youth maintain these cultural ties and helps by infusing Aboriginal history and culture in the curriculum and by encouraging activities such as field trips and presentations. The MacPhail Aboriginal Pride Programs in Calgary strive to “achieve higher graduation rates, have consistent attendance rates, and experience a sense of pride in their culture and a willingness to share their culture with non-aboriginal peers and families.”